A review of Malaysian medicinal plants with potential anticancer activity - Muhammad Ashraf Aiman Mat Jusoh; Farizan Aris; Mohd Taufiq Mat Jalil; Khairunnisa Ahmad Kamil; Nurul Aili Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2023)
The global cancer incidence and its high mortality rate indicate limitations in its current treatment and chemotherapeutic strategies. This sparked a worldwide interest in the demand for chemical diversity in searching for therapeutic drugs derived from natural products. Natural products from medicinal plants, whether as pure compounds or crude extracts, offer inexhaustible sources of new drugs because of their unparalleled chemical diversity. This review aims to disseminate detailed information on the anticancer potential of Malaysian medicinal plants, focusing on the bioactive phytochemicals and mechanisms of action against cancer development in both in vitro and in vivo studies. A comprehensive search of PubMed, Google Scholar, Scopus, and ScienceDirect databases was conducted to find relevant articles on the anticancer activity of Malaysian medicinal plants. A total of hundred and twenty-two (122) articles on the anticancer activity of Malaysian medicinal plants was identified and reviewed. Eighty-five (85) plants (in vitro) and 16 plants (in vivo) have been identified to possess anticancer activity. The activity reported was attributed primarily to diverse chemical groups of naturally occurring phytochemicals such as flavonoids, phenolics, glycosides, quercetin, and gallic acid. Henceforth, the findings will hope to aid further research in understanding the underlaying mechanism and the efficiency of the isolation of the bioactive compounds.